Treatment goals and their attainment: a structured approach to assessment and evaluation. (1st February 2016) - Ramnerö, Jonas; Jansson, Billy
Abstract: Treatment goals are considered a vital part of therapeutic work, and their role is often emphasized in cognitive behavioural therapy (CBT). However, the attainment of goals is rarely accounted for in terms of treatment outcome. In this study, we set out to investigate a structured format for goal assessment and goal attainment in CBT delivered as routine care. We were especially interested in the sensitivity to change in perceived goal attainment. Patients completed a self-administered version of the Bern Inventory of Treatment Goals (BIT-C) and rated their perceived attainment on a maximum of five prioritized goals before and after 12 weeks of treatment, along with measures on anxiety, depression and health-related quality of life. The results indicated that the prioritized goals only partially correspond to disorder-specific concerns, and that perceived proximity to treatment goals is clearly associated with improvements following treatment. The results are discussed in terms of the BIT-C being a promising tool for use in clinical settings in assessing treatment goals as well as in evaluating the attainment of these goals.